PELAKSANAAN KURIKULUM 2013 DALAM MATA PELAJARAN PENGANTAR AKUNTANSI DI KELAS X SMKN 1 JAWAI SELATAN - Sarifah, Sarifah; Ulfah, Maria; Achmadi, Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the implementation of the curriculum 2013 in the field of business and management expertise in the introductory subjects of accounting in the class X SMK Negeri 1 Jawai Selatan Sambas District. The research method used is case study with qualitative research. Sources of data of this research is data source that is teacher of introduction subject of accountancy in class X field of business expertise and management of research result show implementation of curriculum 2013 in applying of competency standard of graduate in class x accounting in introductory subject of accountancy have been done well, in accounting x class on accounting introductory subjects have also been implemented well, then the application of standard processes in class x accounting on the subjects of accounting introduction has not been done well, and the application of assessment standards in class x accounting on the subjects of accounting introduction has not been done with good .Â Keywords: Implementation of Curriculum 2013, Introduction to Accounting